Strategies for the synthesis of brevipolides - Kurniawan, Yudhi Dwi; Rosyidah, A'liyatur (Beilstein Journal of Organic Chemistry, 2021)
In recent years fifteen 5,6-dihydro-α-pyrone derivatives, bearing either a distinctive cyclopropane or furan ring and named brevipolides A–O (1–15), have been isolated from the invasive plant Hyptis brevipes Poit. Their fascinating structural features, and the potent biological activities, including cytotoxicity against an array of human cancer cell lines and inhibition of the chemokine receptor CCR5, make them attractive synthetic targets. This review article highlights the recent synthetic methodologies and briefly summarizes their biological activities.
Keywords: brevipolides; 5,6-dihydro-α-pyrone; Furukawa-modified Simmons–Smith cyclopropanation; Hyptis brevipes Poit; ring-closing metathesis

(untitled) - Suárez-Ortiz, G. A.; Cerda-García-Rojas, C. M.; Fragoso-Serrano, M.; Pereda-Miranda, R. (J. Nat. Prod., 2017)

(untitled) - Xu, D.-H.; Huang, Y.-S.; Jiang, D.-Q.; Yuan, K. (Pharm. Biol. (Abingdon, U. K.), 2013)

(untitled) - Bhuiyan, M. N. I.; Begum, J.; Nandi, N. C. (J. Med. Plants Res., 2010)

(untitled) - Deng, Y.; Balunas, M. J.; Kim, J.-A.; Lantvit, D. D.; Chin, Y.-W.; Chai, H.; Sugiarso, S.; Kardono, L. B. S.; Fong, H. H. S.; Pezzuto, J. M.; Swanson, S. M.; Carcache de Blanco, E. J.; et al. (J. Nat. Prod., 2009)

(untitled) - Limachi, I.; Condo, C.; Palma, C.; Nina, N.; Salamanca, E.; Ticona, J. C.; Udaeta, E.; Flores, N.; Serato, A.; Marupa, N.; Chao, B.; Ibaguari, G.; et al. (Nat. Prod. Commun., 2019)

(untitled) - Falah, F.; Hadiwibowo, N. (Indones. J. For. Res., 2017)

(untitled) - Sakr, H. H.; Roshdy, S. H.; El-Seedi, H. R. (J. Appl. Pharm. Sci., 2013)

(untitled) - Roosita, K.; Kusharto, C. M.; Sekiyama, M.; Fachrurozi, Y.; Ohtsuka, R. (J. Ethnopharmacol., 2008)

(untitled) - Gupta, M. P.; Monge, A.; Karikas, G. A.; Lopez de Cerain, A.; Solis, P. N.; de Leon, E.; Trujillo, M.; Suarez, O.; Wilson, F.; Montenegro, G.; Noriega, Y.; Santana, A. I.; et al. (Int. J. Pharmacogn. (Lisse, Neth.), 1996)

(untitled) - Goun, E.; Cunningham, G.; Chu, D.; Nguyen, C.; Miles, D. (Fitoterapia, 2003)

(untitled) - Hegde, V. R.; Pu, H.; Patel, M.; Das, P. R.; Strizki, J.; Gullo, V. P.; Chou, C.-C.; Buevich, A. V.; Chan, T.-M. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Suárez-Ortiz, G. A.; Cerda-García-Rojas, C. M.; Hernández-Rojas, A.; Pereda-Miranda, R. (J. Nat. Prod., 2013)

(untitled) - Mohapatra, D. K.; Kanikarapu, S.; Naidu, P. R.; Yadav, J. S. (Tetrahedron Lett., 2015)

(untitled) - Kumaraswamy, G.; Jayaprakash, N.; Rambabu, D.; Ganguly, A.; Banerjee, R. (Org. Biomol. Chem., 2014)

(untitled) - Chen, C.-N.; Hou, D.-R. (Org. Biomol. Chem., 2016)

(untitled) - Lin, J.-W.; Kurniawan, Y. D.; Chang, W.-J.; Leu, W.-J.; Chan, S.-H.; Hou, D.-R. (Org. Lett., 2014)

(untitled) - Shiva Raju, K.; Sabitha, G. (Org. Biomol. Chem., 2017)

(untitled) - Raju, K. S.; Sabitha, G. (Tetrahedron Lett., 2018)

(untitled) - Sheng, Y.-H.; Leu, W.-J.; Chen, C.-N.; Hsu, J.-L.; Liu, Y.-T.; Hsu, L.-C.; Hou, D.-R.; Guh, J.-H. (Molecules, 2020)

High-Throughput Screening Assays in Toxicology - Sakamuru, S.; Attene-Ramos, M. S.; Xia, M. (Mitochondrial Membrane Potential Assay, 2016)

(untitled) - Borges, D. G. L.; Echeverria, J. T.; de Oliveira, T. L.; Heckler, R. P.; de Freitas, M. G.; Damasceno-Junior, G. A.; Carollo, C. A.; Borges, F. d. A. (PLoS One, 2019)

(untitled) - Gennari, S. M.; Vieira Bressan, M. C. R.; Rogero, J. R.; MacLean, J. M.; Duncan, J. L. (Vet. Parasitol., 1991)